Endurance performance: Genes or gene combinations? - Gomez-Gallego, F.; Santiago, C.; Gonzalez-Freire, M.; Muniesa, C. A.; Fernandez del Valle, M.; Perez, M.; Foster, C.; Lucia, A. (International Journal of Sports Medicine, 2009)
We assessed the possible association between variants of the genes encoding for the angiotensin-converting enzyme (ACE) and a-actinin-3 (ACTN3) (both individually and combined) and several endurance phenotypic traits, e.g., peak power output (PPO), ventilatory (VT) and respiratory compensation threshold (RCT), among others, in professional road cyclists and sedentary controls (n = 46 each). We applied an ANCOVA test using the aforementioned phenotype traits as dependent variables, ACE and/or ACTN3 genotype as the fixed (independent) factor and age and body mass as covariates. We only found a significant genotype effect with no concomitant covariate effect for ACTN3, with cyclists who were not a-actinin-3 deficient (RR + RX genotypes) having higher PPO and VT values than their XX counterparts (mean [SEM]: 7.4 (0.1) vs. 7.1 (0.1) W/kg, p = 0.035; and 4.5 (0.1) vs. 4.3 (0.1) W/kg, p = 0.029, respectively). Cyclists with an "extreme" ACTN3 and ACE genotype combination, i.e., most strength/power oriented (DD + RR/RX), had higher RCT values than those with the "intermediate" combinations (II + RX/RR, p = 0.036; and DD + XX, p = .0004) but similar to those with the most endurance oriented genotype (II + XX). No significant differences (p > 0.05) were found in controls. In summary, in world-class cyclists, we only found an association between ACTN3 genotypes and VT and PPO, and between ACTN3/ACE genotype combinations and RCT.